The Effect Of immune molecules in protection against COVID 19 - Njum, Ali Anok; Rima N. Hassan (International Journal of Psychosocial Rehabilitation, 2020)
project attempts to estimate the manifestation of stimulated indicators on pBL ,as the manifestation of CD45 & CD74 in patients infected with COVID19 assessment of TNF-α and IL-8 serum ranks in patients with COVID 19 , associate the consequences of pBL –stimulation indicators appearance and serological valuation of TNF-α &IL-8 using multiple infection phases. A total of (24) positive patients for COVID19 were screened for this study .Patients attended general lab. of Al-Muthanna province , because of abdominal pain ,pulmonary distress , fever and coughing any samples expressed positive for COVID19 directly choose to show level of TNF-α & IL-8 in serum of patient and show expression of CD45 and CD74 in pBL in HCV patients. Results showed that serum samples were analyzed for IL-8 & TNF-α by ELISA , showed highly significant increases (p<0.05) in serum level of covid 19 patients as compared with healthy control groups , acute covid 19 revealed high as well as , increases in serum level of TNF-α significantly(p<0.05) ,while moderate cases of disease express high increase in serum level of IL-8 significantly(p<0.05).Activated markers study revealed high expression of CD74 & CD45 in covid 19 patients as compared with healthy normal groups ,where acute covid 19 patients were showed significantly(p<0.05) high expression in CD74 & CD45 compared with other covid 19 patients .